Rancang Bangun Alat Pengisian Stroom Token Otomatis kWh Meter Digital - Vistarika; Rizadi Sasmita Darwis (ABEC Indonesia, 2021)
Electricity has now become a necessity that cannot be released in everyday life. Gradually, now PLN electricity customers are starting to use a prepaid electricity system, which requires customers to enter a token code via the keypad on the digital kWh meter before using it. This tool is designed to be able to fill stroom tokens automatically using the smart kWh application which will make it easier to fill electricity tokens wherever and whenever. In the process of pressing the digital kWh meter button using 12 solenoids, each of which will be placed right in front of the kWh meter button and by using the raspberry pi as a microprocessor that can trigger the solenoid movement via the relay driver. This tool can fill the electricity token stroom to completion with an average time required of 27.74 seconds with a delay between solenoids of approximately 1.3 seconds. Based on the results of testing and data analysis, the percentage value of the accuracy of the tool in filling the electricity token stroom at the kWh meter is 92%. Meanwhile, the error percentage of the tool in filling the electricity token stroom is an error of 8%. By using a solar cell, this tool will continue to work optimally when the power goes out and with this tool, the process of filling the electricity token stroom is simply done through the smart kWh application.